Distribution and bioavailability of chromium in contaminated soils by tannery residues - Santos, Ademir Dos [UNESP]; De Oliveira, Luciana Camargo [UNESP]; Botero, Wander Gustavo [UNESP]; Mendonça, André Gustavo Ribeiro [UNESP]; Santos, Felipe André Dos [UNESP]; Rocha, Julio Cesar [UNESP]; Ribeiro, Maria Lúcia; De Oliveira, Alessandro Silva (FapUNIFESP (SciELO), 2009)
Samples of soil, water and sediment were collected and analyzed in order to evaluate chromium, contamination due to deposition of tannery residues onto soils under different management regimes. The results showed that soils used for sugar cane cultivation were not adversely impacted. However, in the case of mango plantations, variable concentrations of chromium, were measured in the soil profile, with 22.2% of values being higher than permitted legal limits, and 38.9% being at levels requiring remediation. Concentrations of bioavailable chromium were lower than the detection limit of the method (0.01 mg of chromium kg-1 of soil), indicating that all of the chromium, present in the samples was either complexed or in an insoluble form. Chromium concentrations measured in samples of water and sediments were indicative of low mobility of the metal in. soils. The main cause of differences found between soil, samples obtained from different cultivations was the type of soil management.
Distribuição e biodisponibilidade de crómio em solos contaminados por resíduos de couro
Keywords: Chromium; Environmental contamination; Tannery residues